2021
DOI: 10.1093/ndt/gfab290
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and non-pharmacological treatments for restless legs syndrome in end-stage kidney disease: a systematic review and component network meta-analysis

Abstract: Background Restless legs syndrome (RLS) is common among patients with end stage kidney disease (ESKD) and is associated with poor outcomes. Several recently published studies had focused on pharmacological and nonpharmacological treatments of RLS, but an updated meta-analysis has not been conducted. Methods The study population was adult ESKD patients on dialysis with RLS. Randomized controlled trials were selected. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…In specific conditions such as chronic kidney disease, aerobic exercises associated with resistance exercise reduced the severity of WED 405 symptoms; but the studies comprised only small samples and the conclusions are still uncertain. A later meta-analysis in the same population confirmed that lower limb stretching exercises performed during dialysis were effective in reducing the severity of the symptoms of the disease 406 . A group of researchers investigated the therapies most commonly used by patients to improve and alleviate the symptoms of WED and found that deep massage was used as a therapy in approximately 77% of cases, although the relief was momentary 407 .…”
Section: Willis-ekbom Disease and Periodic Limb Movement Disordermentioning
confidence: 86%
See 1 more Smart Citation
“…In specific conditions such as chronic kidney disease, aerobic exercises associated with resistance exercise reduced the severity of WED 405 symptoms; but the studies comprised only small samples and the conclusions are still uncertain. A later meta-analysis in the same population confirmed that lower limb stretching exercises performed during dialysis were effective in reducing the severity of the symptoms of the disease 406 . A group of researchers investigated the therapies most commonly used by patients to improve and alleviate the symptoms of WED and found that deep massage was used as a therapy in approximately 77% of cases, although the relief was momentary 407 .…”
Section: Willis-ekbom Disease and Periodic Limb Movement Disordermentioning
confidence: 86%
“…First, the interaction with the medical team for receiving supportive information about the proposed treatment is crucial. Second, several studies have shown significant improvements in the symptoms of WED and PLMD following the use of non-pharmacological therapies for their treatment [403][404][405][406][407][408] . Since WED improves with movement, the hypothesis that exercise improves the disease has been tested, with promising findings in different populations (Table 22).…”
Section: Role Of the Physical Therapistmentioning
confidence: 99%
“…RLS seriously affects the life quality and prognosis of patients. Several studies had focused on pharmacological and nonpharmacological treatments of RLS and showed that gabapentin is the most effective pharmacologic intervention which also might improve sleep quality ( 22 ). However, there is still a lack of effective treatment measure ( 23 ), and it's important to understand the pathogenesis of RLS.…”
Section: Discussionmentioning
confidence: 99%
“…22 Cool dialysate (35.5°C) in comparison with standard (37°C) dialysate led to RLS severity score reduction and represents a reasonable choice of a nonpharmacological approach for patients with RLS on dialysis. 23 4. Intradialytic exercise with resistance training is safe, effective, and should be offered more regularly A.…”
Section: E Vitamin C and Vitamin E Supplementation And Cool Dialysate...mentioning
confidence: 99%
“… 22 Cool dialysate (35.5°C) in comparison with standard (37°C) dialysate led to RLS severity score reduction and represents a reasonable choice of a nonpharmacological approach for patients with RLS on dialysis. 23 …”
mentioning
confidence: 99%